Thalamic germinoma: a challenging diagnosis, case report and literature review. Issue 7 (3rd July 2018) - Khairy, Sami; Khubrani, Reham; Al-Dandan, Sadeq; Alobaid, Abdullah
Abstract: The thalamus and basal ganglia are unusual locations for an intracranial germ cell tumors. We are reporting a rare case of thalamic germinoma in an 18-year-old male. Challenging presentation, radiological appearance and pathological finding after surgical intervention delayed the diagnosis and treatment. Also, we are providing an extensive literature review. Diagnosis of thalamic germinoma is challenging because of non-specific symptoms, rare location and inconclusive radiological findings. An early tissue diagnosis associated with good outcome.